Exploration of Niskāma Karma in the Śrimad Bhāgavata-Gītā - Pokhrel, Mohan Kumar (Dristikon: A Multidisciplinary Journal, 2022)
This exploratory study deals with the depiction of karma theory from Śrī Kṛṣṇa to Arjuna before the commencement of the Mahābhārata war. The philosophy of niskāma karma is a doctrine to consider being the ground stone of the entire Hindu philosophical outlook. The theory of karma is based on the niskām-karma. This research article addresses human beings to give up the attachment and the fruit regarding the karma. The objectives of this research are to highlight the importance of niskāma karma for human beings and to show how Śrī Kṛṣṇa motivates Arjuna to perform niskām-karma. The analysis is primarily based on Swāmī Vevekānanda's karma theory which confirms the realization of righteousness and God from niskāma karma. The researcher has used English translation of the Sanskrit text of Franklin Edgerton as the primary text. The findings of this investigation endow with evidences that the text has used niskāma karma to motivate human beings to do the same for self-satisfaction, righteousness, and justice in society following the footsteps of Śrī Kṛṣṇa. The conclusion of this article suggests that Śrī Kṛṣṇa is a far-sighted first motivational speaker of the earth to improve the activities of human beings and for the establishment of peace, justice, and righteousness on the earth.